Community Study of Local Fruit Producing Trees of Economic Value in Uraur Village, West Seram District - Aprilsya, Kristin; Tuhumuri, Evelin; Lapu, Petrus (RUMPHIUS, 2025)
Local fruit is one type of natural wealth in Indonesia which has many benefits in the economic sector. Local fruit plants in Indonesia are a fairly large source of income in the agricultural sector to help the community's economy, especially the people of Maluku Province. Uraur Village is one of the villages in Maluku Province. This research aims to determine and explain the community structure and habitat of local fruit-producing trees, including tree types, number of individuals, density, frequency, dominance, importance value index and diversity index. The method used is quantitative descriptive. The environmental parameters measured are soil and air temperature, soil and air humidity, pH and light intensity. The results of this research found 19 types of local fruit plants with 12 families and 12 genera with species diversity belonging to the medium category. Environmental parameters at the research location support the growth of local fruit plants because the habitat at the research location is relatively good. Air temperature ranges from 29-35oC, soil temperature ranges from 28.4-32.16oC, air humidity ranges from 44-68%, soil moisture ranges from 28.4-32.2%, pH 7 and light intensity ranges from 694 -1541 lux.